Examining the Interrelationships Between Reading Self-Concept, Reading Motivation, and Reading Comprehension in Yayasan Islamiyah Palembang - Meidiana Eka Putri; Masita Arianie; Melli Kusmaningrum; Khoirunnisa; Aprilia Sari Rahayu; Wela Aulia; Aryawira Pratama (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyse the relationship between reading self-concept and reading comprehension, the relationship between reading motivation and reading comprehension, and the contribution of reading self-concept and reading motivation to students’ reading comprehension. This study employs a quantitative approach with a correlational design. The research subjects consisted of 264 students from MTs Negeri Palembang who were selected as the research sample. Data were collected through a reading self-concept questionnaire, a reading motivation questionnaire, and a reading comprehension test. Data analysis was conducted using Pearson’s Product Moment correlation and regression analysis. The results of the study indicate that reading self-concept has a positive and significant correlation of moderate strength with students’ reading comprehension. Reading motivation also shows a positive and significant correlation of moderate strength with reading comprehension. Furthermore, the results of the regression analysis indicate that reading self-concept and reading motivation together account for 7.9% of the variance in students’ reading comprehension. These findings suggest that although the direction of the relationship between the two independent variables is positive, the strength of the correlation is relatively low, meaning their influence on reading comprehension remains limited. Therefore, other, more dominant factors influencing students’ reading comprehension should be considered.